Korupsi Penyalahgunaan Wewenang Perspektif Belom Bahadat - citranu citranu (Tampung Penyang, 2020)
This article to purpose determine the corruption of the abuse of authority and sanctions according to the Belom Bahadat principle. The study used is a normative legal study with the type of conceptual approach, doctrinal approach and statute approach. The results of this study include corruption in the abuse of authority violating the Belom Bahadat principle because corruption in the abuse of authority is a crime and is contrary to the appropriateness values and the order of life of the Dayak adat people, as well as the application of sanctions to corruptors who abuse the authority to obtain criminal charges and applying compensation.